Smart Cities can Benefit from Energy Savings Made Possible by Spending on Intelligent Transportation System for Society 5.0 - Mahat, Dipak; Reeya Agrawal (MultiTech Publisher, 2024)
Studies highlighted the interconnectedness of Intelligent Transportation Systems (ITS), Smart Cities, and Society 5.0, envisioning a future where these concepts collectively propel urban development. The study emphasized the role of ITS in Society 5.0, promoting safer, more efficient, and environmentally friendly transportation options. The methodology entailed a thorough review of academic sources and a variety of data collection methods. The findings indicated an increased reliance on ITS in smart cities, with a focus on adapting to multiple information sources. The discussion emphasized the critical role of ITS in achieving Society 5.0's goals, establishing a synergistic path for innovative, human-centric urban environments. Overall, the study envisions a future in which seamless integration of technology within smart cities improves urban mobility, reduces congestion, and promotes data-driven decision-making for societal progress.